GAMBARAN KARAKTERISTIK AKSEPTOR KB SUNTIK DI RUMAH BERSALIN CITRA PALEMBANG - Petrianasari Petrianasari; Dini Anggraini (Jurnal Kesehatan Abdurrahman, 2012)
Family Planning (KB) according to World Health Organization (WHO) expert commite was an evaluation in helping acouple of husband and wife for gaining certain objects in partus and pregnancy case.The research used descriptive method. The population of this research was all the injection KB acceptor who investigating their in Citra Midwifery Health Center Palembang 2010 and the research was condutted ini June 2010. The variable of this research was independent variabel, age, the data were analyzed through univariat analysis, frequensy distribution from independen and dependen variabels.The results analysis from 30 respondences,found that there were 73.3% respondensces by using old injection contraception tools, respondences in mother was 20-35 years old, 66.7%, 43.3% less less comprehension 43.3%,and unoccupated mother 93,3%. The Mothers who investigating their health in Citra Midwifery Health Center Lebong Siarang Palembang 2010 who become injection KB acceptor was all the was 66,7% in 20-35 years old. And for the old mother was 33,3% in > 35 years old. The mothers with less comprehension 43,3%, with well comprehnsion 36,7% and with enough comprehension wa 20,0%. The unccupated mother was 28 peoples (93,3%) and for occupated mother 6,7%.The suggestion for citra midwifery health center in palembang hoped that the health server could give more health information through councelling to the mother about KB especially injection contraception tools. For Abdurahman Midwifery Academy Palembang as an aducation instrution could more colledted the library sources in library, so that it can be used for the next researcher escpecially about family plannin and also for the next research it was hoped that they could preparation for the research and for the education could gained the great expected result.